Classification of Cleft Lip/Palate: Then and Now. (March 2017) - Allori, Alexander C.; Mulliken, John B.; Meara, John G.; Shusterman, Stephen; Marcus, Jeffrey R.
Cleft lip and/or palate (CL/P) is phenotypically diverse, making classification difficult. This article explores the evolution of ideas regarding CL/P classification and includes the schemes described byDavis and Ritchie (1922), Brophy (1923), Veau (1931), Fogh-Andersen (1943), Kernahan and Stark (1958), Harkins et al. (1962), Broadbent et al. (1968), Spina (1973), and others. Based on these systems, a longhand structured form is proposed for describing CL/P in a way that is clear, comprehensive, and consistent. A complementary shorthand notation is also described to improve the utility and convenience of this structured form.